Joint contractures in severe burn patients with early rehabilitation intervention in one of the largest burn intensive care unit in China: a descriptive analysis. Issue 1 (20th May 2019) - Tan, Jianglin; Chen, Jian; Zhou, Junyi; Song, Huapei; Deng, Huan; Ao, Ming; Luo, Gaoxing; Wu, Jun
Abstract: Background: Joint contracture is the major clinical complication in burn patients, especially, the severe burn patients. This study aimed to investigate the number and severity of joint contractures in patients with burns affecting greater than or equal to 50% of the total body surface area (TBSA) undergoing early rehabilitation in a burn intensive care unit (BICU). Methods: We analyzed burn patients with burns affecting greater than or equal to 50% of the TBSA admitted to a BICU who received early rehabilitation within 7 days post-injury from January 2011 to December 2015. Demographic and medical information was collected. The range of motion (ROM) of different joints was measured 1 month post-admission. Spearman's correlation coefficient and logistic regression analysis was used to determine predictors of the presence and severity of contractures. Result: The average affected TBSA of the included burn patients was 67.4%, and the average length of stay in the BICU was 46.2 ± 28.8 days. One hundred and one of 108 burn patients (93.5%) developed at least one joint contracture. The ROM in 67.9% of the affected joints was mildly limited. The majority of contractures in severe burn patients were mild (37.7%) or moderate (33.2%). The wrist was the most commonly affected joint (18.2%), followed by the shoulder, ankle, hip, knee, and elbow. A predictor of the presence of contractures was the length of hospital stay ( p  = 0.049). The severe contracture was related to the area of full-thickness burns, the strict bed rest time, and the duration of rehabilitation in BICU. The length of rehabilitation stay (days) in patients with moderate contracture is 54.5% longer than that in severe contracture ( p  = 0.024) Conclusion: During the long stay in BICU, the length of rehabilitation stay in a BICU could decrease the severity of contractures from severe to moderate in the patients with equal to 50% of the TBSA. Hence, this research reveals the important role of early rehabilitation interventions in severe burn patients.